Development of a Textbook for Critical Reading of Legal Documents in Compulsory University Courses in Higher Education - Triwati Rahayu; Suryadi Suryadi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to develop a legal document-based critical reading textbook in compulsory university courses in higher education. This study used a research and development method with the ADDIE model. The instruments used to obtain research data are observation guidelines, interviews, and expert assessment questionnaires for the developed products. The subjects of this research were students of the law study program who were taking Indonesian language courses at Ahmad Dahlan University Yogyakarta. The data analysis technique used was quantitative descriptive data analysis. The results of this study indicated that the product feasibility test for material experts obtained a score of 3.6 in the excellent category. The product feasibility test for media experts obtained a score of 4.0 with a good category. Based on the student response test results calculated by the AIKEN V formula, the score was 0.95 to 1 with an outstanding category. The effectiveness test using independent sample pretest results 0.155 means insignificant, meaning that the initial conditions are not different or the same. In contrast, the post-test results of 0.011 mean significant, meaning different conditions. This study concludes that the textbook developed is influential for teaching material for students of law study programs in understanding legal documents.